2015
DOI: 10.1016/j.pjnns.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Writing in Richardson variant of progressive supranuclear palsy in comparison to progressive non-fluent aphasia

Abstract: As omission errors predominate in writing of patients with PSP-RS, writing seems to be compromised mainly because of oculomotor deficits, that may alter visual feedback while writing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In a comparison of written picture descriptions in patients with nfvPPA to patients with progressive supranuclear palsy (PSP) and controls, patients with nfvPPA have reduced length, speed, and information units compared to controls, 6 as well as reduced number of written words compared to PSP. 7 Long term follow-up of written language in one patient with nfvPPA also showed a decrease in written word output and amount of information, as well as a decrease in sentence complexity over time and increased dependence on nouns over verbs. 8 A study comparing written picture descriptions of patients with lvPPA to those of amnestic mild cognitive impairment (MCI) and dementia likely due to Alzheimer Disease reported that patients with lvPPA had increased letter insertion errors and a higher verb use.…”
Section: Introductionmentioning
confidence: 91%
“…In a comparison of written picture descriptions in patients with nfvPPA to patients with progressive supranuclear palsy (PSP) and controls, patients with nfvPPA have reduced length, speed, and information units compared to controls, 6 as well as reduced number of written words compared to PSP. 7 Long term follow-up of written language in one patient with nfvPPA also showed a decrease in written word output and amount of information, as well as a decrease in sentence complexity over time and increased dependence on nouns over verbs. 8 A study comparing written picture descriptions of patients with lvPPA to those of amnestic mild cognitive impairment (MCI) and dementia likely due to Alzheimer Disease reported that patients with lvPPA had increased letter insertion errors and a higher verb use.…”
Section: Introductionmentioning
confidence: 91%
“…In a comparison of written picture descriptions in patients with nfvPPA to patients with progressive supranuclear palsy (PSP) and controls, patients with nfvPPA showed reduced length, speed and information units compared to controls, 6 as well as reduced number of written words compared to PSP. 7 Long-term follow-up of written language in one patient with nfvPPA also showed a decrease in written word output and amount of information, as well as a decrease in sentence complexity over time and increased dependence on nouns over verbs. 8 A study comparing written picture descriptions of patients with lvPPA to those of amnestic mild cognitive impairment (MCI) and dementia likely due to Alzheimer’s disease reported that patients with lvPPA had increased letter insertion errors and a higher verb use.…”
Section: Introductionmentioning
confidence: 92%
“…Dysgraphia is common in PSPs and CBS [36,51], and may be due to linguistic, cognitive, visual, or motor impairment. Writing features noted in PSPs include micrographia, abnormal slanting, omission of letters and words, addition of letters, and omission of diacritic marks in a Polish-language group [36,59,96,118,119]. The micrographia of PSPs differs from Parkinson's disease by the absence of progressive fatigue (reducing letter size).…”
Section: Writingmentioning
confidence: 99%
“…The micrographia of PSPs differs from Parkinson's disease by the absence of progressive fatigue (reducing letter size). The dysgraphia in PSPs may result from visuo-constructional or oculomotor deficits, whereby abnormal vertical and horizontal saccades disrupt the visual monitoring of writing [36,118], and may be exacerbated by severe limb akinesia.…”
Section: Writingmentioning
confidence: 99%